Feminism In Indian Literary Works: A Study of Feminism in Indian Literature (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The feminist movement,"includes any form of opposition to any form of social, personal oreconomic discrimination which women suffer because of their sex."(2), sosays David Bouchier in the "Introduction" to his book The FeministChallenge. The desire for equality with men on the social and politicalfronts took the form of an organised movement in the west. It includes both thestruggle for women's equal rights as well as the aspirations and strivingstowards the all round liberation of women, which is considered as emancipation.